Lead-Reversal ECG Simulating Myocardial Infarction A Case Report and Literature Review - Amin, Mohammad Gaffar; Chowdhury, Abdul Wadud; Ahmed, Mohsin; Sabah, Khandker Md Nurus; Haque, Hasna Fahmima; Kabir, Syed Rezwan; Islam, Kazi Nazrul; Saleh, Mohammad Abaye Deen (Bangladesh Heart Journal, 2017)
Electrocardiogram (ECG) is one of the most important and time-tested tool for appropriate interpretation and diagnosis of coronary artery disease (CAD) and other structural & electrical cardiac abnormalities. Erroneous misplacement of surface ECG-leads (lead reversal) may result in wrong interpretation as well as unnecessary investigations, admission to hospital and improper treatment. Early & prompt recognition of lead-reversal is imperative to avoid inappropriate & harmful therapeutic interventions to the patients. This casereport focuses on an interesting scenario of ECG-lead misplacement, which will aid in detection, exclusion and further prevention of ECG lead misplacement. Bangladesh Heart Journal 2016; 31(2) : 104-108